Kepentingan komunikasi dalam latihan = The importance of communication in training - Abdul Manan, Kamaruzzaman; Ahmad, Che Mahzan (2018)
This study examines the effect of communication in training learning exercise. Training is one of the main methods for the organization to deliver important information to employees so that their work performances are in line with the organisation goals. This research aims to highlight the role of communication in the training course that believed to have a strong relationship, but it is often neglected and underestimated. This study uses Social Learning Theory by Albert Bandura as research framework that includes three factors namely communication in training environment factor, independent learning factor and behavioural factor. The study also examined the relationship for each element in the communication in training environment factor with factor of independent learning and behavioural factor to further understand the importance of communication on the effectiveness of training. This research used survey and distributing questionnaires as the method in collecting the data to 200 respondents that attended the 5S training program. This study manage to proves that communication in training environment factor have a strong relationship with the independent learning factor and behavioural factor. In addition, this study has also found that communications are fundamental factors that need to be prioritized to ensure the success of the organisational training programme. Moreover, this study also successfully strengthens the gap between the field of communication studies and management studies, which indeed have a very close relationship. *****************************************************